(untitled) (Contemporary Mathematics, 2024)
Solar thermal systems utilize solar energy to generate heat, and the incorporation of nanoparticles such as Al2O3-Cu-Ni with a water base can elevate their efficiency. These nanofluids, composed of aluminum oxide, copper, and nickel nanoparticles dispersed in water, enhance heat absorption and transfer within the system. This improvement contributes to heightened overall performance and effectiveness of solar thermal systems. Cupronickel alloy helps in the process of desalination. Hence, this study examines the heat exchange properties in the context of a boundary layer flow of a trihybrid over a variable-thickness Riga plate stretched and heated by convective heat with non-Newtonian fluid (Jeffery) in the presence of thermal radiation. The governing equations of the boundary layer are transformed into a system of ordinary differential equations through appropriate similarity transformations, and those equations are resolved utilizing a boundary value problem program. The engineering parameters are analyzed through the application of multiple linear regression. The key finding of the investigation is that the Prandtl number, and thickness index number all have a positive impact on the Nusselt number. The presence of radiation and a uniform heat source improves the Nusselt number, physically this energy transfer improvement assists in higher solar collector efficacy; and converts that energy to usable heat. The rationale behind selecting trihybrid nanoparticles Al2O3, Cu, and Ni lies in the balance and inertness of Al2O3, with metals Cu, and Ni, both possessing more thermal conductivity.